Artificial Intelligence and its Impact on Family Interaction Patterns and the Construction of Children's Gender Identity -A Sociological Analytical Study - . Noura Issa Alwan Al-Tamimi, Asst. Lecturer (lark, 2026)
The contemporary world is witnessing a number of negative transformations in the structure of social relations due to the rapid developments in artificial intelligence, which has not remained confined to the technological field but has extended into the family sphere, affecting patterns of interaction and communication between individuals. Smart applications, digital content aimed at children, and virtual assistants have helped to reshape methods of socialization and directly influence the process of building children's gender identity. The research aimed to analyze the positions of the governing authorities on the family interaction and explore its role in shaping children's gender identity from an analytical sociological perspective. This was achieved by studying the symbolic and cognitive relationships that arise between humans and technology within the family sphere and the resulting transformations in roles, freedom, and social values. The research adopted a descriptive analytical approach based on analyzing the relevant social networks and partnerships. The research reached a set of results, including that artificial intelligence has become a living social network that helps to define the concepts of parental point of view, privacy, and identity within the family It also considers the production of exclusive entertainment images through dialogue, skeet, and targeted content, which may reinforce or perpetuate certain gender stereotypes. The study also considered the nature of use and family culture, as well as the need to build a social and educational foundation among parents and children, resulting in conscious engagement with smart media that maintains a balance between traditional values ​​and digital transformations.
Keywords: Keywords: Artificial Intelligence; Digital Family; Gender Identity; Heritage Values